Upside down management revolutionizing management and development maximize business success - Lorriman, John (McGraw-Hill, 1995)
This plan for business success stresses three key areas: the importance of the individual's commitment to improvement; allowing all employees the opportunity to learn at the fastest possible rate; and the role of manager as developer, coach and facilitator of the organization's goals.